Ranging Method for Navigation Based on High-Speed Frequency-Hopping Signal - En Yuan; Wangdong Qi; Peng Liu; Li Wei; Longliang Chen (IEEE Access, 2018)
The lack of sufficient spectral resources in many alternative positioning, navigation, and timing (APNT) systems for aviation has led to the problem of mutual interferences. Building APNT system with the cognitive radio and frequency-hopping (FH) techniques can resolve above problem, however, the main challenge is to achieve a long and high-precision range with high-speed FH signals. In this paper, we propose a novel ranging method called time–frequency matrix ranging (TFMR), which is based on the FH signals. Using the TFMR method, we built a jam-resistant APNT system to meet the accuracy and coverage requirements of aviation. We employed a dual-tone signal for the TFMR to estimate the pseudoranges between the ground stations and the aircrafts. One major challenge we faced was that what was good for ranging accuracy was bad for coverage. For example, increasing the dual-tone interval can improve the ranging accuracy; however, this led to a decrease in the unambiguous measurement range (UMR). To overcome this challenge, we employed different dual-tone intervals in different hops of the frequency-hopping signal. Finally, we formed a time–frequency matrix, so that a high UMR could be guaranteed without any harmful consequences on the ranging accuracy in the middle to high levels of the signal-to-noise ratio. The Cramér–Rao lower bound of TFMR is derived as the benchmark of the method. Using extensive simulations, we investigated the ranging performance of the TFMR method. The simulation results showed that the proposed TFMR could satisfy the APNT requirements of the Federal Aviation Administration.